Beyond Anything Realism Can Represent? Monstrous Crime in Marx’s Victorian Novel - Jayson Althofer (Humanities)
This article reads Karl Marx’s Capital (volume 1, 1867) as the Bildungsroman of a congenital criminal: its eponymous character, Capital. Following Friedrich Engels’s The Condition of the Working Class in England (1845), Marx detects and dissects capitalism’s crimes. Capital has been called Marx’s ‘Victorian novel’ and compared to English realism’s triple-deckers. Yet his indispensable informants include factory inspectors whose reports, according to Fredric Jameson, provide testimony beyond anything realism can represent. How, then, does Marx’s apparently realist aesthetic convey Capital’s criminal deeds and criminogenic drive? To address this matter, the article examines the Gothicism of Marx’s realism. It highlights his development of Engels’s Gothic realism, demonstrates how Capital begins in media res—its first sentence presenting an immense, monstrous collection of evidence of Capital’s cannibalism—and links this opening crime scene to Marx’s portrayal of the 1863 case of Mary Anne Walkley. Murdered in her workplace, Walkley inhabits an underworld overpopulated by fellow workers killed by wage-labour. The article argues that, because actuality under the rule of Capital is structurally and monstrously criminal, Marx’s Gothic constitutes a realistic medium to represent criminal monsters and structures.